Comparing Performance of Government and Private Clients in Construction Projects: Contractors’ Perspective - Jati Utomo Dwi Hatmoko; Riqi Radian Khasania (Institute of Research and Community Outreach - Petra Christian University, 2016)
By nature, government and private projects have different characteristics, which influence client performance. This research aims to compare performance of government and private clients in construction projects as perceived by contractors. Six client performance indicators were used, i.e. understanding of project requirements, financial, decision making, management skills, supports for contractor, and client’s attitude. Data were collected through questionnaire surveys filled in by 117 respondents. The results show that there is a significant difference between both types of client performance. Three variables related to financial indicators, i.e. timely payment, owner value estimate, and payment approval, rank in the bottom three of the government client performance, but in contrast rank in the top three of the private ones. These results suggest that the government clients’ performance is perceived inferior to the private ones. Establishing a clients’ forum for sharing knowledge and best practices would be a strategic solution to enhance clients’ capacities.